Central Giant Cell Granuloma of the Posterior Maxilla: A Case Report - Ebrahimi, Hooman (Tabriz University of Medical Sciences, 2008)
Central giant cell granuloma (CGCG), formerly called giant cell reparative granuloma, is a non-neoplastic proliferative lesion of unknown etiol-ogy. It occurs most commonly in the mandible. The case reported here resembled a wide variety of conditions that led to a misdiagnosis both on clinical and radiographic examinations but was histopathologically diagnosed as CGCG. We describe a case of CGCG arising from the poste-rior maxilla to highlight the importance of histo-pathology in the diagnosis of this enigmatic le-sion.